On Trump's New Call to Terror and Resistance Like Harriet Tubman - Clyde Lanford Smith (Social Medicine Publication Group, 2020)
The US President has trumpeted his threat to visit systemic terror Sunday 7/14/19 on the homes of families where one or another person does not have their immigration papers in order. The threat has brought distress, panic even, to many in the USA. Perhaps campaign strategy, the rhetoric and its effect hearken to Dred Scott Days (the period after the U.S. Supreme Court Decision "Dred Scott vs. Sandford," March 6th, 1857) when persons abetting escaped slaves avoid re-capture were themselves considered law-breakers and punished. As if in flash-back, persons in our time who provide refugees water in Arizona's desert are targeted with prison. But today's refugee-hunters count driver's license photo facial recognition software (notorious for increased mis-identification with People of Color, a new spin on the "crime" of "Driving While Black") in their civil rights dismantling tool-kit.